2018
DOI: 10.1158/1078-0432.ccr-17-1725
|View full text |Cite
|
Sign up to set email alerts
|

High Yield of Pathogenic Germline Mutations Causative or Likely Causative of the Cancer Phenotype in Selected Children with Cancer

Abstract: In many children with cancer and characteristics suggestive of a genetic predisposition syndrome, the genetic cause is still unknown. We studied the yield of pathogenic mutations by applying whole-exome sequencing on a selected cohort of children with cancer. To identify mutations in known and novel cancer-predisposing genes, we performed trio-based whole-exome sequencing on germline DNA of 40 selected children and their parents. These children were diagnosed with cancer and had at least one of the following f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 42 publications
3
66
0
Order By: Relevance
“…We have recently shown that clinical exome sequencing is an effective strategy for the diagnosis of known and novel genetic tumor predisposition syndromes. 20 Here, we report how application of exome sequencing in two centers independently resulted in the identification of pathogenic TRIM28 frameshift mutations in two families with very similar clinical presentations of Wilms tumor. A subsequent screening of a validation cohort revealed seven additional individuals with germline mutations, and one individual with a somatic mutation in TRIM28.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…We have recently shown that clinical exome sequencing is an effective strategy for the diagnosis of known and novel genetic tumor predisposition syndromes. 20 Here, we report how application of exome sequencing in two centers independently resulted in the identification of pathogenic TRIM28 frameshift mutations in two families with very similar clinical presentations of Wilms tumor. A subsequent screening of a validation cohort revealed seven additional individuals with germline mutations, and one individual with a somatic mutation in TRIM28.…”
Section: Discussionmentioning
confidence: 95%
“…Data analysis focused on shared variants between the siblings and revealed a heterozygous c.246_247del variant in the TRIM28 gene, predicted to cause a frameshift and premature stop codon after 6 amino acids p.(Cys83Phefs*6) (NM_005762.2). No other variants of interest were identified …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The genes with the highest number of reported germline variants included TP53 , NF1 and BRCA2 40. The other study selected 40 childhood cancer patients with a suspected genetic predisposition to cancer, detecting pathogenic or likely pathogenic germline variants in 20% (8/40) of patients with childhood cancer 41. Of the 146 genes considered for initial investigation, germline variants were reported in five genes ( DICER1 , CHEK2 , APC , BRCA2 and TP53 ) 41.…”
Section: Discussionmentioning
confidence: 99%
“…The other study selected 40 childhood cancer patients with a suspected genetic predisposition to cancer, detecting pathogenic or likely pathogenic germline variants in 20% (8/40) of patients with childhood cancer 41. Of the 146 genes considered for initial investigation, germline variants were reported in five genes ( DICER1 , CHEK2 , APC , BRCA2 and TP53 ) 41. Both studies detected heterozygous germline variants in 1.3% (12/914) or 7.5% (3/40) of patients, respectively, in genes primarily associated with predisposition to adult cancer ( BRCA2 , MSH2 , MSH6 , PMS2 and CHEK2 ) 40 41…”
Section: Discussionmentioning
confidence: 99%